TRAINS MOVEMENT PUNCTUALITY (Perner's Contacts, 2010)
This article is about a train punctuality and about a part of the fare refundationat higher quality trains (EC, IC) travelling in Slovakia.. It is in need of a roundingrules and a part of returned fare to state
Keywords: the railway transport; the fare and IC train